Monetary policy strategy of the NBRM: experiences and options - Aneta Krstevska (National Bank of the Republic of Macedonia, 2007)
National Bank of the Republic of Macedonia (NBRM) has been implementing an exchange rate targeting strategy for a more then a decade and so far it proved to be very successful. The aim of this paper is shortly to explain the advantages of this strategy and moreover to put more focus on the analysis for peg sustainability. Also, the paper discusses the effectiveness of the interest rate transmission channel in Macedonian economy. Based on the analysis for peg sustainability and still existing problems in the functioning of the interest rate transmission channel, the main findings are that current monetary policy strategy is still valid and regular monitoring of the environment that is changing dynamically is more then necessary.
Keywords: 330; Geldpolitisches Ziel; Wechselkurspolitik; Geldpolitische Transmission; Mazedonien